A direct approach to achieving efficient free-form shells with embedded geometrical patterns. (April 2023) - Meng, Xianchuan; Zhang, Li-Yuan; Zhao, Zi-Long; Xie, Yi Min
Abstract: Shells are widely used in architectural and engineering design due to their appealing geometry and efficient structural form. However, designing free-form shells with specific geometrical patterns remains a challenging issue as both aesthetical and mechanical properties need to be considered. Based on structural topology optimization, this paper develops a direct approach to generating high-performance shells with embedded geometrical patterns. In this approach, graph theory and the nonuniform rational basis spline (NURBS) method are combined to produce parametric designs based on polygonal meshes. This approach is capable of optimizing shells with complicated geometry and different thicknesses. The effectiveness of the approach is demonstrated by three representative examples. The techniques developed in this study can be used to design efficient free-form shells for construction. Highlights: A direct approach is developed to design free-form shells with embedded geometrical patterns. The NURBS method and graph theory are combined to produce parametric designs based on polygonal meshes. This approach is capable of optimizing shells with different thicknesses.